Efficacy of two brands of Mebendazole (500 mg) in the treatment of Ascaris lumbricoides and hookworm infection among school-aged children in South Gondar zone, Northwest Ethiopia: a randomized open label trial - Birhanu Malede; Ayalew Jejaw Zeleke; Yenesew Mihret Wondmagegn; Abebaw Setegn; Hailegebriel Wondimu; Ayenew Berhan; Tadesse Misganaw; Gashaw Azanaw Amare; Tegegne Eshetu (BMC Infectious Diseases)
Abstract Background Parasitic worms remain a serious public health problem in developing countries. Mebendazole is a widely used anthelmintic, but variations in drug efficacy among different brands of mebendazole may impact treatment outcomes. This trial investigated efficacy of two different brands of mebendazole (Vermox® and X-WORM®) used in the deworming program and available in local pharmaceutical shops. Methods A randomized, open label trial was conducted among 212 children in Alember and Addis Zemen primary schools. Convenient sampling technique was used to select schools and study participants. McMaster egg counting technique was used to determine the intensity of infection. Eligible Ascaris lumbricoides or hookworm infected study participants were randomized into either a single dose of 500 mg Vermox® or X-WORM® mebendazole treatment arm. Follow-up data were collected between 14 and 21 days after treatment. Egg reduction rate was primary outcome and cure rate was used as secondary outcome, Paired sample t-test was used to determine egg reduction rate, and odds ratio was used to determine cure rate. Results A total of 212 school-aged children participated in the study, of which 106 school-aged children were infected by Ascaris lumbricoides and the remaining 106 were infected by hookworm parasites. From each Ascaris lumbricoides and hookworm infection group 53 school-aged children received Vermox®, and the remaining 53 school-aged children received X-WORM® 500 mg mebendazole. The egg reduction rate of Vermox® against Ascaris lumbricoides was 97.63% (95% CI: 86.1-108.7), while that of X-WORM® was 95.87% (95% CI: 85.1-106.9). For hookworm the egg reduction rate of Vermox® was 74.96% (95% CI 65.6–85.2), while that of X-WORM® was 71.5% (95% CI: 61.5–81.6). The cure rate of Vermox® and X-WORM® against hookworm was 29.4% (95% CI: 17.6–43.1) and 27.5% (95% CI: 15.7–39.2), respectively. Against Ascaris lumbricoides the cure rates were 92.3% (95% CI: 84.6–98.1) for Vermox® and 90.4% (95% CI: 82.7–98.1) for X-WORM®. Conclusion and recommendation The efficacy of both brands of mebendazole against Ascaris lumbricoides and hookworm infections showed a satisfactory level based on the egg reduction rate. However, the cure rates against hookworm remains questionable, despite all study participants having light-intensity infections, which are generally expected to respond well to treatment. Further investigation is needed to evaluate the therapeutic outcomes of mebendazole in cases of moderate and heavy infection intensity to generate stronger evidence. Trial registry This trial was retrospectively registered on https://pactr.samrc.ac.za/ and the unique identification number for registry was PACTR202503808932606 and the registration date was 27 March 2025.